"Wieczór" Edwarda Żebrowskiego - autorska kopia - Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Edward Żebrowski’s “Evening” – the Creative Copy The aim of this article is interpretation of the short film directed in 1964 by Edward Żebrowski, student of Film School in Łódź. Author is considering the many aspects of the relationships between study film and two years earlier debut of Roman Polanski, the famous Knife in the Water. He shows that by using the concept of feature of more experienced colleague, Żebrowski at the same time creates the foundations for his own film language and manifests its own perception of the world, as well as interpersonal problems, developed in further work.